2020
DOI: 10.24891/re.18.12.2354
|View full text |Cite
|
Sign up to set email alerts
|

The Smart Sustainable City concept: A system of indicators to assess the regional sustainability and development adaptability

Abstract: Subject. This article discusses the issues related to the digital development of cities and regions. Objectives. The article aims to create a system of indicators to assess the capacity of smart resilience of Russian cities. Methods. To create such a system, we analyzed the standards developed by the International Organization for Standardization (ISO), International Telecommunication Union (ITU), and the European Telecommunications Standards Institute (ETSI). Results. The article proposes a system of indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are many reasons. Their analysis [1,2,3,4] showed that in all cases there was no comprehensive approach to the structure of urban real estate. In some cases, the administrative center dominated, in others innovative, in the third residential development, etc.…”
Section: Methodsmentioning
confidence: 99%
“…There are many reasons. Their analysis [1,2,3,4] showed that in all cases there was no comprehensive approach to the structure of urban real estate. In some cases, the administrative center dominated, in others innovative, in the third residential development, etc.…”
Section: Methodsmentioning
confidence: 99%
“…The natural complex's ecological capacity depends on the volumes of the leading natural reservoirs-the air basin, water bodies, watercourses, land areas, and soil reserves-as well as the biomass of flora and fauna. Additionally, the capacity of biogeochemical fluxes that renew the contents of these reservoirs, including the rate of local atmospheric gas exchange, replenishment of clean water volumes, soil formation processes, and the productivity of biota, plays a crucial role [27]. Anthropogenic impact has pushed the natural complex of the territory to its limit of stability, which has resulted in excessive levels of variability.…”
Section: Existing and Potential Environmental Impact Assessmentmentioning
confidence: 99%
“…Other authors believe that a city that is not sustainable is not really "smart", and the role of technology in smart cities should be to ensure the sustainable development of cities, not new technology as an end. Representatives of this approach believe that a "sustainable smart city" is defined as the goal of balanced development and relying on technology in solving social, economic, and environmental problems to improve the quality of life of the population, increase the efficiency of urban management and build up the economic, technological and intellectual potential of the city (Akimova et al, 2020). They also note that such a city involves building a complex structure of relationships between various synergistic clusters with the help of ICT, allowing the creation, application, and dissemination of solutions that help ensure a favorable living environment in the city and achieve the SDGs (Bibri and Krogstie, 2017).…”
Section: Development?mentioning
confidence: 99%